Optimalisasi Partisipasi Masyarakat dalam Layanan Informasi Publik Digital PPID Diskominfo Kabupaten Badung - Wulandari, Ni Putu Riska; Prabawati , Ni Putu Anik (Lenggogeni Data Publishing, 2025)
This study examines public participation in digital public information services provided through the website of the Information and Documentation Management Officer (PPID) of the Communication and Informatics Office of Badung Regency using a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and document analysis and analyzed using the e-Participation framework developed by Tambouris et al. (2008), which consists of the stages of e-informing, e-consulting, e-involving, e-collaborating, and e-empowerment. The findings indicate that, at the institutional level, PPID of Badung Regency has fulfilled the stages of e-Participation through proactive public information disclosure and the provision of responsive digital service mechanisms. Nevertheless, public participation remains largely concentrated at the levels of information access and oversight and has not yet developed optimally toward collaboration and empowerment. This study concludes that the digitalization of public information services has been implemented normatively but has not fully generated substantive public participation. Strengthening digital literacy, enhancing two-way interactions, and institutionalizing sustainable feedback mechanisms are therefore essential to fostering more inclusive and accountable public participation. Abstrak Penelitian ini mengkaji partisipasi masyarakat dalam layanan informasi publik digital melalui website PPID Dinas Komunikasi dan Informatika Kabupaten Badung dengan pendekatan kualitatif deskriptif. Data dikumpulkan melalui wawancara mendalam, observasi, dan studi dokumentasi, kemudian dianalisis menggunakan kerangka e-Participation Tambouris et al. (2008). yang meliputi e-informing, e-consulting, e-involving, e-collaborating, dan e-empowerment. Hasil penelitian menunjukkan bahwa PPID Kabupaten Badung telah memenuhi tahapan e-Participation secara kelembagaan melalui penyediaan informasi publik yang proaktif dan dukungan layanan digital yang responsif. Namun, partisipasi masyarakat masih dominan pada tahap akses informasi dan pengawasan, serta belum berkembang secara optimal ke arah kolaborasi dan pemberdayaan. Penelitian ini menegaskan bahwa digitalisasi layanan informasi publik telah berjalan secara normatif, tetapi belum sepenuhnya menghasilkan partisipasi publik yang substantif. Penguatan literasi digital, intensifikasi interaksi dua arah, dan pelembagaan mekanisme umpan balik berkelanjutan menjadi prasyarat penting untuk mendorong partisipasi masyarakat yang lebih inklusif dan akuntabel. Kata kunci: PPID, keterbukaan informasi publik, partisipasi masyarakat, e-participation, pemerintahan digital.